Calculation of Passenger Type Car Insurance Based on Frequency Data and Claim Size - Wandira, Ika (iora, 2025)
Calculation of motor vehicle insurance risk premiums is an important aspect in the insurance industry, which functions to determine the amount of premium to be paid by the policyholder. This study aims to analyze how the calculation of risk premiums is carried out using claim frequency data and claim amounts as the main basis for determining fair premiums and in accordance with the risks faced by insurance companies. Through this calculation model, insurance companies can estimate the amount of risk faced and set proportional premiums. The data used in this study are assumption data that refer to historical claims to provide an overview of accurate and realistic premium calculations in the context of motor vehicle insurance. The results of the calculation of motor vehicle insurance risk premiums with Total Loss Only (TLO) protection are influenced by the frequency and amount of claims. Analysis of claim data for the 2015-2020 period shows an increasing trend in the average claim amount from IDR 8,000,000 to IDR 10,000,000, while the average annual premium is relatively stable at IDR 1,200,000. Risk premiums increase as the number of claims increases, so companies need to allocate sufficient funds to cover these risks. In addition, the increasing frequency of claims each year indicates a higher risk for the company